Exploring physical activity trends and lesson context of incarcerated youth in a sport-leadership program. (15th November 2022) - Wahl-Alexander, Zachary; Anderson, Jared; Jacobs, Jennifer
Summary: Incarcerated youth are one subset of the population in dire need of physical activity interventions. As inactivity within incarcerated populations has become a mounting public health concern, several sport-based physical activity and fitness programs within prisons have emerged. The purpose of this study is to explore physical activity levels and lesson context of a sport-leadership program in one juvenile detention center. Participants in this study were 27 incarcerated males ( M age = 19.3), imprisoned in one juvenile detention center. Participants participated in 20, 40-min sport-leadership lessons over the course of 3 months. Each lesson was live coded using the System for Observing Instructional Time (SOFIT) to examine physical activity levels and lesson context. Over the course of 20 lessons, participants engaged in moderate to vigorous physical activity (MVPA) for 61% of lesson time (24.5 min). Further, over 23% of lesson time was spent vigorously (9.5 min). Specific to lesson context, 18% of total lesson time (7.5 min) was spent in management whereas 7.96% (3.1 min) was consumed by knowledge acquisition. Furthermore, a vast majority of each session (70%) was spent in gameplay (28.04 min). This study is the first to adopt the SOFIT systematic observation instrument to evaluate and quantify MVPA and lesson context during a sport-leadership program within a juvenile detention center. Results from this study indicate incarcerated youth who participated in this program engaged in MVPA for more than 60% of lesson time. It was reported that overall MVPA of participants within programming slightly decreased across the 20 total lessons.